Methods Of Increasing Students' Interest In Knowledge - Z. Rahmonova (Genius Publishing Group, 2024)
In the conditions of today's globalization, youth education and education of our country has been raised to the level of state policy, and on the basis of this, it is one of our main tasks to protect young people, who are the creators of our future, from various foreign ideas, ideologies and aggressions aimed at occupying the human heart and mind. Already, as the President of the Republic of Uzbekistan Shavkat Mirziyoyev noted, "Education and education of the young generation has always been important and relevant
Keywords: Education; human